KRISIS ETIKA KONSTITUSIONAL DALAM PRAKTIK KETATANEGARAAN INDONESIA KONTEMPORER - Marfuah; FITRI ELFIANI (Fakultas Hukum Universitas Pasir Pengaraian, 2026)
This study aims to critically examine the crisis of constitutional ethics in contemporary Indonesian constitutional practice, which is characterized by a distortion between constitutional norms as a source of ethical values and the pragmatic, formalistic exercise of state power. This research employs a normative legal method with statutory, conceptual, and case approaches, supported by a socio-legal perspective to analyze the gap between normative frameworks and actual practices. The findings reveal that the crisis of constitutional ethics manifests in various forms, including the politicization of constitutional interpretation, the weakening of checks and balances, the rise of excessive legal formalism that neglects substantive justice, and the low integrity of state officials. A prominent example is the Putusan Mahkamah Konstitusi Nomor 90/PUU-XXI/2023, which has sparked controversy regarding the independence and ethical conduct of the constitutional court. This condition indicates that the constitution is increasingly reduced to a formal legal instrument to legitimize political interests, thereby weakening democratic quality and public trust. Therefore, a reconstruction of constitutional ethics is necessary through strengthening institutional integrity, reforming constitutional interpretation toward substantive justice, and internalizing constitutional values within legal and political culture. This study is expected to contribute both theoretically and practically to strengthening the rule of law and substantive democracy in Indonesia.